Curcumin prevents the bile reflux‐induced NF‐κB‐related mRNA oncogenic phenotype, in human hypopharyngeal cells. Issue 9 (17th June 2018) - Vageli, Dimitra P.; Doukas, Sotirios G.; Spock, Todd; Sasaki, Clarence T.
Abstract: The presence of bile is not an uncommon finding in acidic oesophageal and extra‐oesophageal refluxate, possibly affecting the hypopharyngeal mucosa and leading to neoplastic events. We recently demonstrated that acidic bile (pH ≤ 4.0) can induce NF‐κB activation and oncogenic mRNA phenotype in normal hypopharyngeal cells and generate premalignant changes in treated hypopharyngeal mucosa. We hypothesize that curcumin, a dietary inhibitor of NF‐κB, may effectively inhibit the acidic bile‐induced cancer‐related mRNA phenotype, in treated human hypopharyngeal primary cells (HHPC), supporting its potential preventive use in vivo. Luciferase assay, immunofluorescence, Western blot, qPCR and PCR microarray analysis were used to explore the effect of curcumin in HHPC exposed to bile (400 μmol/L) at acidic and neutral pH. Curcumin successfully inhibited the acidic bile‐induced NF‐κB signalling pathway (25% of analysed genes), and overexpression of NF‐κB transcriptional factors, c‐REL, RELA(p65), anti‐apoptotic bcl‐2, oncogenic TNF‐α, EGFR, STAT3, WNT5A, ΔNp63 and cancer‐related IL‐6. Curcumin effectively reduced bile‐induced bcl‐2 overexpression at both acidic and neutral pH. Our novel findings suggest that, similar to pharmacologic NF‐κB inhibitor, BAY 11‐7082, curcumin can suppress acidic bile‐induced oncogenic mRNA phenotype in hypopharyngeal cells, encouraging its future in vivo pre‐clinical and clinical explorations in prevention of bile reflux‐related pre‐neoplastic events mediated by NF‐κB.